Effect of dopant on ferroelectric, dielectric and photocatalytic properties of Co–La-doped dysprosium chromite prepared via microemulsion route. Issue 21 (1st November 2022) - Maqbool, Humaira; Bibi, Ismat; Nazeer, Zarish; Majid, Farzana; Ata, Sadia; Raza, Qasim; Iqbal, Munawar; Slimani, Yassine; Khan, M.I.; Fatima, Mahvish
Abstract: In the current study, pristine and a series of La and Co-doped dysprosium chromite (Dy1-y Lay Cr1-x Cox O3 ) nanoparticles have been fabricated via a facile microemulsion technique. The influence of doping was evaluated based on structural, ferroelectric, dielectric, and photocatalytic properties. The prepared nanoparticles were characterized by XRD, SEM, Raman, and UV–Vis techniques. XRD patterns confirm the synthesis of a monophase orthorhombic structure with space group Pbnm with an average crystalline size in the 18–37 nm range. The saturation polarization (Ps), remanence (Pr), and coercivity (Hc) were determined using a hysteresis loop, and it was observed that by increasing the concentration of dopants, the value of Ps and Pr were improved. According to the PL spectra, highly substituted materials had a low recombination rate and higher charge separation (e − - h + ), which was ultimately accountable for higher photocatalytic activity. The dielectric loss decreases with frequency and dopant concentration. The photocatalytic activity of Dy1-y Lay Cr1-x Cox O3 was investigated against Crystal Violet (CV) dye under sunlight irradiation. The Dy1-y Lay Cr1-x Cox O3 furnished a 70% dye degradation in 90 min, which is attributed to the tunned bandgap and efficient electron-hole pair separation and the photocatalytic activity under visible light making Dy1-y Lay Cr1-x Cox O3 a promising photocatalyst for dye removal from wastewater.